The recycling through melting Zircaloy machining chips, preliminary results - Luiz Alberto Tavares Pereira; Jesualdo Luiz Rossi (Brazilian Journal of Radiation Sciences)
PWR (Pressurized Water Reactor) reactors employ as nuclear fuel UO2 pellets packed in zirconium alloy tubes, called cladding. In the manufacture of the tubes, machining chips are generated which can not be discarded, since the recycling of this material is strategic in terms of nuclear technology, legislation, economics and the environment. These nuclear alloys are very expensive and are not produced in Brazil and are imported for the manufacture of nuclear fuel. In this work, we will discuss methods not yet studied to recycle Zircaloy chips using electron beam furnaces in order to obtain ingots. In addition, it is intended to carry out the melting of new Zircaloy alloys, from the fusion of zirconium sponge produced in IPEN and imported and Zircaloy bars. The mechanical properties and the present phases of the material should be determined, as well as, the characterization of the microstructures by optical microscopy. This work, therefore, aims at the creation of a new line of research where methods will be approached to recycle the chips and to reduce in 30 times by means of fusion the enormous volume of material stored in the form of machining chips, being able to do others components for nuclear or chemical industry use, as well as conducting basic development research.